(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article explores the linguistic phenomenon of lexical borrowing within costume design terminology, examining how foreign-derived terms have shaped the evolution of fashion language. Borrowings are viewed not merely as adopted vocabulary, but as cultural and conceptual markers that reflect historical interactions, aesthetic traditions, and professional practices in global fashion. The research analyzes dominant donor languages – primarily French and English, and highlights their influence on shaping stylistic norms and semantic structures in the costume design lexicon. The study also discusses how borrowed terms undergo semantic adaptation in recipient languages and gain context-specific meanings. Special attention is given to the integration of foreign fashion terminology in Uzbek and Russian contexts, illustrating the dynamic interplay between global diffusion and local linguistic identity. The findings demonstrate that borrowing serves both communicative efficiency and cultural enrichment, reinforcing the interconnectedness of language, design, and cultural heritage in contemporary fashion discourse.